Pembentukan Karakter Siswa Melalui Keteladanan Guru PAI di SMP Darul Falah Ngadirejo Purwoharjo - M. Zain Kamal; Anas Jauhar Firmansyah; Wildan Nasruloh; Slamet Slamet (CV. Lentera Literasi Indonesia, 2026)
Character education is a fundamental mandate within the national education system, particularly in preparing students to become individuals who are faithful, ethical, and responsible. The role of teachers, especially Islamic Education (PAI) teachers, is highly strategic because their personal example directly influences students’ behavior. In the context of a pesantren-based school, such exemplification becomes even more essential as part of cultivating religious values. This study was conducted at SMP Darul Falah Ngadirejo to examine how PAI teachers shape students’ character through daily acts of role modeling within classroom instruction and school interactions. Employing a descriptive qualitative method with data triangulation through interviews, observations, and document analysis, this research analyzed data using the interactive model of Miles, Huberman, and Saldana, consisting of data reduction, data display, and conclusion drawing. The findings reveal that PAI teachers play a significant role in character formation through exemplary practices in worship, ethics, and social interaction. A religious school environment, pesantren culture, and positive teacher–student relationships serve as major supporting factors, while digital media influence, limited parental supervision, and inconsistency in teacher modeling represent notable challenges.